Management and 5-year outcomes in 9938 women with screen-detected ductal carcinoma in situ: the UK Sloane Project - Thompson, AM; Clements, K; Cheung, S; Pinder, SE; Lawrence, G; Sawyer, E; Kearins, O; Ball, GR; Tomlinson, IPM; Hanby, A; Thomas, JSJ; Maxwell, AJ; et al. (Elsevier, 2018)
Background Management of screen-detected ductal carcinoma in situ (DCIS) remains controversial. Methods A prospective cohort of DCIS diagnosed through the UK National Health Service Breast Screening Programme (1 April 2003 to 31 March 2012) was linked to national databases and case note review to analyse patterns of care, recurrence and mortality. Results Screen-detected DCIS in 9938 women, mean age 60 years (range 46-87), was treated by mastectomy (2931) or breast conservation surgery (BCS) (7007; 70%). At 64 months median follow up, 697 (6.8%) had further DCIS or invasive breast cancer after BCS (7.8%) or mastectomy (4.5%) (p<0.001). Breast radiotherapy (RT) after BCS (4363/7007; 62.3%) was associated with a 3.1% absolute reduction in ipsilateral recurrent DCIS or invasive breast cancer (No RT: 7.2% vs RT: 4.1% (p<0.001) and a 1.9% absolute reduction for ipsilateral invasive breast recurrence (No RT: 3.8% vs RT: 1.9% (p<0.001), independent of excision margin width or size of DCIS. Women without RT after BCS had more ipsilateral breast recurrences (p<0.001) when the radial excision margin was <2mm. Adjuvant endocrine therapy (1208/9938; 12%) was associated with a reduction in any ipsilateral recurrence, whether RT was received (HR 0.57: 95% CI 0.41 - 0.80) or not (HR 0.68: 95% CI 0.51 - 0.91) after BCS. Women who developed invasive breast recurrence had a worse survival than those with recurrent DCIS (p<0.001). Among 321 (3.2%) who died, only 46 deaths were attributed to invasive breast cancer. Conclusion Recurrent DCIS or invasive cancer is uncommon following screen-detected DCIS. Both RT and endocrine therapy were associated with a reduction in further events but not with breast cancer mortality within 5 years of diagnosis. Further research to identify biomarkers of recurrence risk, particularly as invasive disease, is indicated.